Research on optimal layout of cutter-head system of rock tunnel-boring machine based on Archimedes spiral theory. (February 2018) - Chen, Yadong; Wei, Tianhua; Gong, Tianxing
In order to obtain the satisfied rock-breaking requirements, the layout of cutter-head system of tunnel-boring machine are optimized and analysed to work efficiently by the scientific and reasonable design. An integrated method which can optimize exactly the cutter-head system considering equivalent life principle and force balance based on Archimedes spiral theory is proposed in this article. The effect of installation radius of cutter on wear coefficient and tunnelling coefficient is analysed using equivalent life principle. The force balance models are established using optimization of cutter arrangement. The comparison between the simulation and experimental results shows that the kinematic and dynamic of cutter-head system are reasonable based on Archimedes spiral method. It can be concluded that, therefore, the proposed integration method can offer a theoretical foundation and reference for dynamic optimal design for cutter-head system.